1982 Uncovered The Falklands War Mapping Project - Clack, Timothy; Pollard, Tony (2023)
War and its legacy are traumatic to individuals, communities, and landscapes. The impacts last long beyond the events themselves and shape lives and generations. Archaeology has a part to play in the recording of, and recovery from, such trauma. The Falklands War Mapping Project delivers the first intensive archaeological survey of the battlefields of the Falklands War. The project is pioneering in its inclusion of military veterans as part of the core team and unique in being the first to take veterans back to the battlefields on which they fought. Forty years after the events of 1982, the project provides a detailed assessment of the character, location, and condition of structural features and artefacts. The project also develops understandings of the role played by conflict heritage - and of landscapes, finds, and past events - in the recall of personal and collective memories. This sumptuously illustrated book brings together the perspectives of team members, institutional partners and others. It showcases the varied and important contributions archaeology can make beyond understandings of distant events linked to therapeutic progress, coming to terms with traumatic experiences, living with the past in the present, and forging new memories, relations, and futures.